A Numerical Investigation of Sinusoidal Flow in Porous Media with a Simple Cubic Beam Structure at 1 Hz and 100 Hz Under Different Porosity Conditions - Sin-Mao Chen; Boe-Shong Hong; Shiuh-Hwa Shyu (Fluids)
This study aims to clarify how porosity and frequency interact to influence permeability and flow behavior in porous media subjected to sinusoidal pressure variations. Specifically, we investigate oscillatory flow at 1 Hz and 100 Hz under varying porosity conditions using a pore-scale Computational Fluid Dynamics (CFD) model. The model is validated against the Johnson–Koplik–Dashen (JKD) model to ensure accuracy in capturing dynamic permeability. At 1 Hz, where the oscillation period greatly exceeds the system’s time constant <semantics>τ</semantics>, the flow reaches a quasi-steady state with dynamic permeability approximating static permeability. Increasing porosity enhances Darcy velocity, with minimal phase difference between velocity and pressure. At 100 Hz, flow behavior depends on the ratio of the oscillation period <semantics>T</semantics> to <semantics>τ</semantics>. For high porosity (<semantics>φ=0.840</semantics>, <semantics>T≈τ</semantics>), the flow does not fully develop before the pressure gradient reverses, leading to significant phase lag. For low porosity (<semantics>φ=0.370</semantics>, <semantics>T≈12τ</semantics>), the phase lag is smaller but remains non-zero due to the smooth temporal variation in pressure. This work contributes to the understanding of porous flow dynamics by revealing how porosity modulates both the amplitude and phase angle of dynamic permeability in frequency-dependent porous flows, providing a framework for predicting phase lag in frequency-sensitive applications.